What is the meaning and nature of active play for today's children in the UK? - Jago Russell; Fox Kenneth R; Brockman Rowan (BMC, 2011)
Abstract Background Preventing the decline in physical activity which occurs around 10-11 years of age is a public health priority. Physically active play can make unique contributions to children's development which cannot be obtained from more structured forms of physical activity. Encouraging active play in children's leisure time has potential to increase physical activity levels while promoting optimal child development. Aspired wisdom states that contemporary British children no longer play outdoors, but systematic evidence for this is lacking. We need to build a more informed picture of contemporary children's play before we consider interventions to increase it. Methods Eleven focus groups were conducted with 77, 10-11 year old children from four primary schools in Bristol, UK. Focus groups examined: 1) children's perceptions of 'play'; 2) how much of their play is active play; and 3) contexts of children's active play. All focus groups were audio-taped and transcribed verbatim. Data were analysed using a thematic approach. Results Children's perceptions of play were broad and included both physically active and sedentary behaviours. Children reported that they frequently engaged in active play and valued both the physical and social benefits it provided. Whereas boys frequently reported having a 'kick about' or riding bikes as their preferred forms of active play, girls were less likely to report a specific activity. Additionally, boys reported greater independent mobility in their active play compared to girls. Finally, boys were more likely to report playing with neighbourhood friends but girls more frequently reported playing with family members. Conclusions Promoting active play in children's leisure time may increase the physical activity of children, but interventions may need to be tailored according to gender.